EFL Students’ Attitudes toward Informal Digital Learning of English (IDLE) as a Mediation - Ismail, Nika Aulia Anwar; Fauziah; Zaiturrahmi (IPI Garut Press, 2024)
This research aimed to understand student attitudes towards the integration of digital learning in English language education at 1st State Senior High School, Peukan Pidie. Employing a qualitative under case study design combining offline questionnaires and semi-structured interviews to gain a comprehensive understanding of student perspectives. Sixty students participated, providing a rich dataset for analysis. The data from the questionnaires revealed prevalent trends in student attitudes. The interview data underwent thematic analysis, following Braun and Clarke's (2006) methodology, to identify recurring themes and patterns. The findings demonstrated a consistently positive attitude among students toward digital English learning. Participants perceived digital tools as engaging, accessible, and beneficial to their learning. They highlighted the enjoyable and interactive nature of these technologies, emphasizing their ease of use and perceived support in the learning process. This study underscores the potential benefits of strategically integrating digital tools into English language education, reflecting a positive student reception and highlighting the technology's perceived effectiveness in enhancing learning outcomes.